The Era of Endovascular Treatment in Venous Disease: What Can We Do and Who Gets Benefit? - Hariadi Hariawan (ACI (Acta Cardiologia Indonesiana), 2019)
Venous system is very different and more complex than arterial system. To deliver blood against the forces of gravity, venous system rely on valve function and peripheral muscle pump. In acute venous disease, blood becomes stasis and leads to deep vein thrombosis. In chronic condition, clinical manifestation may vary from either venous obstruction or vascular incompetence. In general venous diseases are devided into venous thromboembolism and chronic venous insufficiency.